Mosses of Mantailang with new species records for Crocker Range Park, Sabah, Malaysian Borneo - Suleiman, Monica; Anthony, Florina; Repin, Rimi; Anwar, Irmah (BRIN Publishing (Penerbit BRIN), 2025)
SULEIMAN, M., ANTHONY, F., REPIN, R. & ANWAR, I. 2025. Mosses of Mantailang with new species records for Crocker Range Park, Sabah, Malaysian Borneo. Reinwardtia 24(2): 145‒159. — A two-day bryological survey was conducted in Mantailang of the Crocker Range Park (CRP), Sabah, East Malaysia, during the 2018 Mantailang scientific exploration. The survey aimed to carry out an inventory of mosses in the study area. A total of 89 species from 49 genera and 23 families were identified, with the family Calymperaceae being the most represented. Notably, 11 species were newly recorded for the CRP. Mantailang harbours rare and Bornean endemic species, highlighting the park’s significance as a moss biodiversity hotspot and its importance for bryophyte conservation in Borneo.